Mild behavioral impairment is associated with β‐amyloid but not tau or neurodegeneration in cognitively intact elderly individuals. Issue 1 (8th January 2020) - Lussier, Firoza Z.; Pascoal, Tharick A.; Chamoun, Mira; Therriault, Joseph; Tissot, Cécile; Savard, Mélissa; Kang, Min Su; Mathotaarachchi, Sulantha; Benedet, Andrea L.; Parsons, Marlee; Qureshi, Muhammad Naveed Iqbal; Thomas, Émilie M.; et al.
Abstract: Introduction: Mild behavioral impairment (MBI) is characterized by the emergence of neuropsychiatric symptoms in elderly persons. Here, we examine the associations between MBI and Alzheimer's disease (AD) biomarkers in asymptomatic elderly individuals. Methods: Ninety‐six cognitively normal elderly individuals underwent MRI, [ 18 F]AZD4694 β‐amyloid‐PET, and [ 18 F]MK6240 tau‐PET. MBI was assessed using the MBI Checklist (MBI‐C). Pearson's correlations and voxel‐based regressions were used to evaluate the relationship between MBI‐C score and [ 18 F]AZD4694 retention, [ 18 F]MK6240 retention, and gray matter (GM) volume. Results: Pearson correlations revealed a positive relationship between MBI‐C score and global and striatal [ 18 F]AZD4694 standardized uptake value ratios (SUVRs). Voxel‐based regression analyses revealed a positive correlation between MBI‐C score and [ 18 F]AZD4694 retention. No significant correlations were found between MBI‐C score and [ 18 F]MK6240 retention or GM volume. Conclusion: We demonstrate for the first time a link between MBI and early AD pathology in a cognitively intact elderly population, supporting the use of the MBI‐C as a metric to enhance clinical trial enrolment.